Phytochemical Identification and Characterization of Secondary Metabolites Isolated from Stem Bark of Tadalinu (Grewia Eriocarpa Juss) - Natalia C. Radjah; Febri O. Nitbani; Alfius R. Kale (Journal of Applied Chemical Science, 2013)
The phytochemical tests, isolations, and characterizations of secondary metabolites in methanol extract of stem bark of Tadalinu (Grewia eriocarpa Juss) have been conducted. The aims of the study were to describe the chemical composition of metabolites and to isolate the flavonoid group compounds in the Tadalinu plant. The results showed that the initial phytochemical tests for saponin, tritepenoid, tannin and the group of flavonoid compounds involve antosianidin, flavonol, chalcone and auron extracted were positive. The rendement of methanol-water (v/v) extract was 34.55%. This extract was then partitioned with petroleum ether and chloroform and performed the phytochemical test for the flavonoid contents existed in the water, petroleum ether, and chloroform layers. The water layer was positive for flavonoid but the other layers were negative. The water layer was further used to isolated the flavonoid group compounds contained using chromatography column with silica gel as stationary phase and n-butanol: acetat acid: water (3:1:6) as the mobile phase and yielding 53 fractions. Based on the differences of their colors, those fractions were then collected into 4 fractions; the fraction 2 and 3 were positive for flavonoids. The FT-IR spectrum of both fractions showed that the functional groups of –OH (3423.41 cm-1), C-O (1029.92 cm-1 and 1072.35 cm-1), aromatic C=C (1639.38 cm-1), and aliphatic C-H (2875.67 cm-1 - 2960.53 cm-1) were existed within those both fractions.